Analysis of fractal structure of flocs formed by composite powder flocculant - Fujiwara, Ryoko; Iwasaki, Tomohiro; Jami, Mohammed Saedi; Iwata, Masashi (2018)
Fractal structure of flocs composed of polydisperse primary particles can be described by the theory proposed by Gmachowski. The composite powdered flocculant which contains a larger amount of inorganic and polymeric flocculant could form stronger flocs with smaller fractal dimension.